Biosurfactant Production by Pseudomonas Aeruginosa 181 - Yassin Al-Araji, Laith Issa (2004)
This study involves the screening of biosurfactant producers that have been isolated from crude oil bacteria degraders. The bacteria were isolated by qualitative screening on cetyltrimethylammonium bromide (CTAB) agar plates and quantitative screening for biosurfactant production in liquid media. A biosurfactant producer identified as Pseudomonas aeruginosa 181 was selected for further analysis. Maximum biosurfactant production by Pseudomonas aeruginosa 181 was achieved after 120 h incubation at pH 7.0 and 37°C. Static condition and 5.0% bacterial inoculum’s gave the optimum biosurfactant yield. Culture medium containing glucose as the carbon source; and casamino acids as the organic nitrogen source gave the highest level of biosurfactant production. Corn steep liquor and ammonium nitrate on the other hand inhibited biosurfactant production. However, the addition of metal ions such as Fe, Mg and Mn maximized biosurfactant synthesis.The biosurfactant produced by Pseudomonas aeruginosa 181 was purified to homogeneity by acid precipitation and ammonium sulphate precipitation. Biosurfactant produced byPseudomonas aeruginosa 181 was stable and had a broad range of pH from 3.0 to 12.0 with the maximum activity (Surface Tension reduction and Emulsification Index (E24))exhibited at pH 7.0. The purified biosurfactant had a broad range of temperature and exhibited optimum activity at 30°C. This biosurfactant had high activity compared to many commercial surfactants with 0.1 mg critical micelle concentration (CMC). The purified biosurfactant had a maximum emulsification index (E24) of 86% with hexadecane,followed by 80% with nonane, dodecane,tridecane, pentadecane, octadecane and o- Xylene.Response surface methodology (RSM) was then used to study interactive effects of the parameters (pH, stirring rate, casamino acid concentration and incubation period) on the production of biosurfactants. Generally, simultaneously increasing surface tension reduction and emulsification index (E24) improved yields. Production carried out at larger volumes of 1L using Bioreactor under RSM-optimized conditions yielded 350.22 mg of products after purification by acid precipitation. Identities of isolated products were verified by using TLC, high performance liquid chromatography (HPLC), liquid chromatography–Mass spectrometry (LC-MS), mass spectrometry (MS-MS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and infraredspectroscopy (FT-IR), from analysis carried out the rhamnolipids were monorhamnolipids and dirhamnolipids.